Economic assessment of childhood rotavirus vaccination in Bangladesh - Abdur Razzaque Sarker (Journal of Infection and Public Health, 2023)
Rotavirus is one of the most highly prevalent communicable diseases in Bangladesh. The objective of this study is to evaluate the benefit-cost ratio of childhood rotavirus vaccination program in Bangladesh. A spreadsheet-based model was used to estimate the benefit and cost of a nationwide universal rotavirus vaccination program against rotavirus infections among under-five children in Bangladesh. A benefit-cost analysis was performed to evaluate a universal vaccination program compared with a status quo. Data from various published vaccination-related studies and public reports were used. The introduction of a childhood rotavirus vaccination program in Bangladesh for 14.78 million under-five children is projected to prevent approximately 1.54 million rotavirus cases during the first 2 years including 0.7 million severe rotavirus infections. This study shows that among the WHO-prequalified rotavirus vaccines, the net societal benefit is the highest if the vaccination program adopts ROTAVAC® rather than Rotarix® or ROTASIIL®. For every dollar invested in the outreach-based ROTAVAC® vaccination program, society would gain $2.03 in return, while in a facility-based vaccination program, society would gain up to about $2.2. The findings of this study demonstrate that a universal childhood rotavirus vaccination program is a cost-beneficial investment of public money. Thus, the government should consider the introduction of rotavirus vaccination in their Expanded Program on Immunization since the rotavirus immunization policy in Bangladesh will be economically justifiable.